A Grounded Theory Study from the Perspective of New Teachers on Their Preparedness to Teach in At-Risk Schools in the United States - Copes, Jaracus (ProQuest LLC, 2022)
Teacher attrition has been around since the beginning of American education. Teacher attrition is problematic to the success of students' academic achievement. One perceived way to reduce teacher attrition is through better training during the pre-service phase. The purpose of this study was to explore university-based teacher education programs effects on a new teacher's preparedness to teach critical subject areas in at-risk secondary schools within the United States from the vantage point of the teacher. This study employed a qualitative design specifically using the grounded theory approach. The researcher recruited new teachers, teachers with 3 or less years of classroom experience, who completed a university-based teacher education program and worked in an at-risk school. Participants took part in personal, semi-structured virtual interviews about their teacher education programs. The transcribed interviews were then analyzed using NVivo qualitative analysis software. This research was trying to find out: What knowledge/skills/dispositions does a new teacher need in an at-risk school? The research identified classroom management, special education, self-care (resiliency training), field-based internship (student teaching), practical training and culturally responsive teaching as the knowledge and skills that are critical to their success. The research also found that the participants did not think that teacher education programs had an impact on their disposition. What was propounded from the data will be known as the Skills Proficiency Theory. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]